Sources de Constantin VII Porphyrogénète concernant le passé le plus ancien des Serbes et des Croates - ŽIVKOVIĆ, Tibor (Byzantina Symmeikta, 2010)
THE SOURCES OF CONSTANTINE PORPHYROGENITUS CONCERNING THE EARLIEST HISTORY OF THE SERBS AND CROATS There are eight chapters (29-36) in De Administrando Imperio by Emperor Constantine VII Porphyrogenitus that contain known historical information on the Slavs of the Balkan Peninsula. Commonly accepted knowledge in historiography tells us that Constantine Porphyrogenitus must have used references on the Serbs, the Croats, and other Slavs from the archives of the Imperial Palace and the verbal accounts of Byzantine administrative personnel who were stationed in Dalmatia. However, our analysis of the earliest historical text on the Serbs and the Croats described in chapters 30, 31 and 32 of the DAI has established that oral tradition could not have been the source of the information on the Serbs or the Croats but rather that Constantine utilized a written source with its approximately dated to around 878.The peculiar style of the source focuses on baptism (Conversio Croatorum et Serborum) and the close ties of the Serbs and the Croats with Rome. This style or literary genre – De conversione – did not exist in Byzantium but was well known during early medieval times in the West. The analysis of the aforementioned chapters of the DAI established a high degree of correlation with parts of the text known in historiography under the title – De conversione Bagoariorum et Carantanorum. The connection between De conversione Bagoariorum et Carantanorum and chapters 30, 31, and 32 of the DAI is easily recognised in the conception of the work, and in the annexed parts by the author. It is our conclusion that we can now take a different path in analysing data on the earliest history of the Serbs and the Croats; it is evident that Constantine Porphyrogenitus used the information collected by an anonymous author who had been employed, very likely, as a high commissioner of the Roman Church.